Scheduling of straight multiproduct pipeline systems with multiple-sources and multiple-destinations - Meira, William Hitoshi Tsunoda (2020)
The interest on the optimization techniques with the objective to aid specialists on taking better decisions has received significant attention in the last years, since any improvement on the usage of the available resources can considerably increase the profit of companies, as in the case of transport of oil derivatives through pipeline systems. In the oil supply chain, transportation of products through pipelines is one of the most used distribution modals, justified by its high volumetric capacity, reliability, and safety when compared to other transportation modes. In this context, the objective of this thesis is to develop an optimization-based decision supporting tool for the scheduling of transportation operations and the inventory management of straight multiproduct pipeline systems with multiple-sources and multiple-destinations. Firstly, a solution framework was proposed; it integrates heuristics and Mixed Integer Linear Programming (MILP) models, a matheuristic, to solve the long-term scheduling of the straight pipeline systems with just a single-source. Then, the developed solution framework is extended to solve straight pipeline systems with multiple-sources and multiple-destinations. This framework is divided into two modules: Allocation and Sequencing Module (ASM) and Scheduling Module (SM). The ASM is responsible for scheduling the pumping operations at the initial source that involves determining the product, volume, flow rate, and sequence of batches to be pumped during the time horizon. The SM schedules the delivery operations at each node and the pumping operations of the intermediate sources to be executed during the considered horizon. Several operational aspects of the studied pipeline network have been taken into account, such as simultaneous deliveries and pumping operations, rigorous treatment of forbidden sequences, scheduling of pipeline interruptions, pipeline maintenance periods, tank maintenance periods, pumping flow rate control, rigorous inventory management. The development of this thesis is a collaborative project with the Brazilian oil company (Petrobras) that allowed the validation of the results and the performance of the developed solution framework using real-world data. The obtained results present viable solutions with proper inventory management that can, certainly, aid the system’s specialists in their decision-making process.